Ethyl vanillate confers mating advantage in male Oriental fruit fly. - Hee, Alvin Kah Wei; Tan, Khim Seong; Wee, Suk Ling; Ritsuo, Nishida

(untitled)
Males of the Oriental fruit fly, Bactrocera dorsalis, have been shown to be strongly attracted to the orchid Bulbophyllum elevatopunctatum, by probing on the floral lip, petals and sepals of the flowers. Whilst chemical analyses have demonstrated the presence of methyl eugenol as one of the component of floral volatiles, a novel compound identified as ethyl vanillate (EV) was also detected in a particular variety to be attractive to sexually mature males. Interestingly, we show that males are attracted to feed on EV and current analyses suggest that male flies sequester EV in substantial quantities in to their rectal glands. This is probably the first record of a male attractant with a benzoic ester structure in the Oriental fruit fly. Thus, the attraction of virgin females and males of the Oriental fruit fly to conspecific males fed with EV was investigated using Wind tunnel bioassays. Concomitant with decreasing light intensity, males fed with EV significantly attracted higher numbers of conspecific males and females during mating period at dusk. Large field cage studies also showed that when groups of EV-deprived and EV-fed males were released in the enclosure, significantly higher numbers of EV-fed males were observed and caught in copula than the EV-deprived males. This suggests that EV may possibly act as a male sex pheromone in Oriental fruit fly males in the absence of methyl eugenol. This will be further discussed in light of fruit fly-orchid coevolution.